Organizational communication: Between system law and syntactic function - Ávila González, Rafael (2020)
The old reduction of organizational communication to the domain of administrative action is charging today’s practitioners the accounts corresponding to its theoretical indeterminacy. If the abstractions about its ends and means, with which it was constructed as an instrument, were in themselves a strong limitation for its strict development, the current metamorphosis of global economics and politics seriously jeopardizes the possibilities of its reproduction. epistemological and professional. The challenges to the world today have narrowed the margin of decision in the conventional terms of analytical and functional affiliation, a new theoretical revision and its undeclared assumptions of self-definition seem relevant in order to give it greater consistency and epistemic validity. This paper hopes to be a contribution in that sense.